Facile synthesis of gamma-ketophosphonates by an intermolecular stetter reaction onto vinylphosphonates - Patra, Atanu; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2014)
The atom-economic and practical N-heterocyclic carbene (NHC) catalyzed Stetter reaction for the synthesis of gamma-ketophosphonates by the reaction of aromatic aldehydes with vinylphosphonates is reported. The NHC derived from N-mesitylimidazolium salt (IMes) was an effective catalyst for this transformation, and the products were formed in moderate to good yields.

From insertion to multicomponent coupling: temperature dependent reactions of arynes with aliphatic alcohols - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Mane, Manoj V.; Biju, Akkattu T. (Chemical Communications, 2016)
The temperature dependent selectivity switch in the reaction of arynes with aliphatic alcohols in THF has been reported. At -20 degrees C, arynes smoothly insert into the O-H bond of alcohols to form alkyl aryl ethers. Interestingly, at 60 degrees C, a highly selective multicomponent coupling occurs with the solvent THF acting as the nucleophilic trigger affording (4-(alkoxy)butoxy)arenes.

Facile synthesis of N-acyl 2-aminobenzothiazoles by NHC-catalyzed direct oxidative amidation of aldehydes - Premaletha, Sethulekshmi; Ghosh, Arghya; Joseph, Sumi; Reddy, Santhi Vardhan; Biju, Akkattu T. (Chemical Communications, 2017)
A mild, general, and high yielding synthesis of N-acyl 2-aminobenzothiazoles has been demonstrated by N-heterocyclic carbene (NHC)-organocatalyzed direct amidation of aldehydes with 2-aminobenzothiazoles proceeding via acyl azolium intermediates. The carbene generated from the triazolium salt under oxidative conditions was the key for the success of this reaction. The method was subsequently applied to the synthesis of various biologically important N-acyl 2-aminobenzothiazoles.